2008
DOI: 10.1093/ijlit/ean018
|View full text |Cite
|
Sign up to set email alerts
|

Private Power, Public Interest: An Examination of Search Engine Accountability

Abstract: As information becomes a critical commodity in modern society, the issue is raised whether the entities that manage access to information, that are tools for public discourse and democracy, should be accountable to the public. The Internet has transformed how we communicate, and search engines have emerged as managers of information, organizing and categorizing content in a coherent, accessible manner thereby shaping the Internet user's experience. This article examines whether search engines should have publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Findings such as these reflect increasing concerns about the influence of such algorithmically driven platforms, due in large part to the already ingrained perceptions among users that such search returns represent objective and reliable representations of relevant online content (not unlike the prevailing perceptions that long have surrounded the institution of journalism). In a call for the imposition of public interest obligations on search engines (essentially, treating search engines comparably to another prominent media institution—the broadcast media), Laidlaw () emphasizes that search engines are “authoritative and reliable, and shape public opinion and meaning” (p. 124). In these ways, the algorithms that are at the core of search engines are functioning in a political capacity similar to established media institutions.…”
Section: The Algorithmic Turn In Media and Its Institutional Connectionsmentioning
confidence: 99%
“…Findings such as these reflect increasing concerns about the influence of such algorithmically driven platforms, due in large part to the already ingrained perceptions among users that such search returns represent objective and reliable representations of relevant online content (not unlike the prevailing perceptions that long have surrounded the institution of journalism). In a call for the imposition of public interest obligations on search engines (essentially, treating search engines comparably to another prominent media institution—the broadcast media), Laidlaw () emphasizes that search engines are “authoritative and reliable, and shape public opinion and meaning” (p. 124). In these ways, the algorithms that are at the core of search engines are functioning in a political capacity similar to established media institutions.…”
Section: The Algorithmic Turn In Media and Its Institutional Connectionsmentioning
confidence: 99%
“…Lastowka's (2008) analysis of the leading search engine, which focuses on trademarks, refers to Google's activities, unsurprisingly, as the state ceding its role to ‘Google's Law’ in the title of and introduction to his study, drawing on Lessig's (1999/2006) work on the regulatory role of code. Laidlaw (2008) has suggested that there is a need for ‘public interest duties’ to relate to search engines, citing algorithm design, manual manipulation of rankings, unbiased results and respect for dignity as examples of issues that engage public interest concerns. Like property owners in modern cities, search engine operators resist the idea that they are common carriers or anything like it, and can point to their own status as speakers as compared with ISPs; Google has been a strong advocate of net neutrality, calling for restrictions on ISPs engaging in discriminatory behaviour or pricing regarding particular content or services.…”
Section: Resultsmentioning
confidence: 99%
“…They promote popular opinions and suppress minority voices. Google, for example, discriminates against minority voices through its PageRank algorithm (Introna, 2006;Introna & Nissenbaum, 2000) and manipulates results for advertisement purposes (Edelman, 2011;Laidlaw, 2008). Search engines cooperate with governments' regulatory actions such as censorship (Shade, 1996) and surveillance (Greenwald, 2014), threatening the privacy and safety of citizens engaged in civic activities which authorities find unfavorable.…”
Section: Enhancing Autonomy In Interaction With Technologymentioning
confidence: 99%